Age, Growth and Gonado-somatic Index of the Red Mullet (Mullus barbatus ponticus Essipov, 1927) in the Eastern Black Sea coast of Turkey - Erhan Çiloğlu; Şevkiye Akgümüş (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the age, growth, and gonado-somatic index (GSI) of the Red mullet (Mullus barbatus ponticus Essipov, 1927) from the Eastern Black Sea coast of Turkey were examined. A total of 1466 M. barbatus ponticus were sampled between September 2010 and August 2011 from trammel net landings in Rize. The total length of Red mullet ranged from 7.42 cm to 17.80 cm and weight ranged from 9.59 g to 50.93 g, regardless of the sex. The sex ratio (♂/♀) was 0.46, with almost twice more females than males. The growth performance of M. barbatus ponticus in the study area is similar to that of the western populations of the same sub-species. A closed season of at least three months (from May to July) banning the use of even the stationary fishing gear will be beneficial for the sustainable stock of management of M. barbatus ponticus in the Black Sea.